2005
DOI: 10.1097/00001888-200510000-00016
|View full text |Cite
|
Sign up to set email alerts
|

Learning/Feedback Activities and High-Quality Teaching: Perceptions of Third-Year Medical Students during an Inpatient Rotation

Abstract: Aspects of feedback, giving mini-lectures, and learning test-interpretation skills were the learning and feedback activities associated with students' perceptions of high-quality teaching. In an increasingly time-pressured inpatient environment, clinical educators should understand which activities students value.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
55
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(55 citation statements)
references
References 33 publications
0
55
0
Order By: Relevance
“…(5,7) Recently, in a report about learning and teaching activities among third-year medical students in the United States, the perceptions of the students regarding high-quality teaching were associated with learning how to interpret chest X-rays, among other factors. (4) In addition, a survey involving practicing physicians in the United States revealed that they believed that formal instruction in radiology should be mandatory in medical schools. (20) In Brazil, unlike in countries with higher income, radiology training is not mandatory in undergraduate medical courses.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…(5,7) Recently, in a report about learning and teaching activities among third-year medical students in the United States, the perceptions of the students regarding high-quality teaching were associated with learning how to interpret chest X-rays, among other factors. (4) In addition, a survey involving practicing physicians in the United States revealed that they believed that formal instruction in radiology should be mandatory in medical schools. (20) In Brazil, unlike in countries with higher income, radiology training is not mandatory in undergraduate medical courses.…”
Section: Resultsmentioning
confidence: 99%
“…(3)(4)(5)(6)(7)(8)(9)(10)(11)(12) In addition, with the worldwide challenge posed by TB, the issue of the interpretation of chest X-rays for the diagnosis of TB reappears in national programs for TB control. (13) In Brazil, the TB challenge has yet to be met, and, to our knowledge, neither physicians nor medical students have been surveyed on their chest X-ray interpretation skills.…”
Section: Introductionmentioning
confidence: 99%
“…Likewise, a positive work setting then allows for continuous and real-time feedback to occur without the fear of looking bad on the wards. Another study involving medical students demonstrated that high-quality teaching was occurring when feedback was common in the daily workplace (Torre et al 2005). Feedback has already been validated in numerous studies as an instrument of instruction in medical training (Ende 1983;Bing-You 1993;Litzelman et al 1998;Furney at al.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, IM residents experience conflicts inherent to their simultaneous commitment to learning, teaching, and service that may undermine both their effectiveness in supervising interns and their own professional development (Yedidia et al 1995). Unfortunately, the defined teaching strategies in medicine have been extrapolated mostly from observations of attending physicians (Irby 1978(Irby , 1994McLean 2001;Torre et al 2005), with none focusing on residents themselves as the teachers. Indeed, attending physicians and residents face different challenges in education under current duty hour restrictions, and the teaching strategies used by both may be divergent due to this (Coverdill et al 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Studies of precepting behaviors published in the medical [8][9][10][11][12][13][14][15][16][17][18] and nursing [19][20][21] literature most frequently require student or resident response to a series of educator-defined value statements, [8][9][10][11][12][13][14][15][16][17][18][19] but there may be other characteristics valued by students not represented in the educator-defined value statements. Student-defined value statements about medical and nursing preceptor behaviors are derived from qualitative studies where open-ended statements made by medical students or residents on their evaluation are analyzed and used to identify what students valued (or didn't) about their preceptors.…”
Section: Introductionmentioning
confidence: 99%